Evaluation of Phytochemical (Quantitative) determination & Anti-oxidant (In-Vitro) activity of ethanolic extract of Bambusa Arundinacea young shoots - Chobdar, Jitendra; Vaghela, Jai Singh (Asian Journal of Pharmaceutical Research and Development, 2024)
Bambusa Arundinaceae (Bamboo), a member of the Graminae family, is utilized in Indian folk medicine to treat a variety of inflammatory disorders. It is used to treat heart, brain, and liver problems throughout India. The current study was conducted to assess the antioxidant activity of an ethanolic extract of young shoots from Bambusa arundinaceae. Material and method: The antioxidant activity of the ethanolic extract was assessed using antioxidant assays such as DPPH, lipid peroxidation, and ferric reducing power assays. The Total Phenolic (TPC) and Total Flavonoid contents (TFC) of all fractions were also evaluated. Result: This study found that ethanolic extracts of young shoots from Bambusa Arundinaceae contained significant amounts of phenolic and flavonoid content. The ethanolic extract has significant antioxidant action. The high flavonoid and phenolic content may account for its antioxidant action. Conclusion: The current study proves that ethanolic extract of young shoots of Bambusa Arundinaceae are an encouraging source of natural antioxidants that could be used in functional foods and nutraceutical products.